Energy Justice Across Borders - Bombaerts, Gunter; Jenkins, Kirsten; Sanusi, Yekeen A.; Guoyu, Wang.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book is open access under a CC BY 4.0 license. We must find new and innovative ways of conceptualizing transboundary energy issues, of embedding concerns of ethics or justice into energy policy, and of operationalizing response to them. This book stems from the emergent gap; the need for comparative approaches to energy justice, and for those that consider ethical traditions that go beyond the classical Western approach. This edited volume unites the fields of energy justice and comparative philosophy to provide an overarching global perspective and approach to applying energy ethics. We contribute to this purpose in four sections: setting the scene, practice, applying theory to practice, and theoretical approaches. Through the chapters featured in the volume, we position the book as one that contributes to energy justice scholarship across borders of nations, borders of ways of thinking and borders of disciplines. The outcome will be of interest to undergraduate and graduate students studying energy justice, ethics and environment, as well as energy scholars, policy makers, and energy analysts.
Section 1-Introduction -- Chapter 1-Where are we now? justice and energy transitions -- Chapter 2-Ethics without borders-world ethics, comparative philosophy, intercultural ethics for energy transitions -- Section 2-African Philosophy -- Chapter 3-Exploring marginalisation and exclusion in renewable energy development in Africa -- Chapter 4-South Africa's renewable energy independent power producer procurement programme -- Chapter 5-The role of energy technology in quality of life and well being in North Africa -- Section 3-Asian philosophy -- Chapter 6-Chinese energy evaluations -- Chapter 7-Energy ethics and Indian philosophical traditions -- Chapter 8-A question of energy ethics-the creative orthodoxy of Buddhist monks in Mongolia -- Section 4-European ethics -- Chapter 9-Contemporary European approaches to energy ethics -- Chapter 10-Energy ethics in the United Kingdom and the Netherlands -- Section 5-South America -- Chapter 11-Latin American principles and environmental ethics -- Chapter 12-Native Americans and energy development -- Section 6-Theistic traditions -- Chapter 13-(Energy) justice in theistic traditions -- Section 7-Conclusion.
Keywords: Technology -- Moral and ethical aspects; Energy policy; Energy and state; Economic geography; Renewable energy sources; Sustainability; Electric power production; Ethics of Technology; Energy Policy, Economics and Management; Economic Geography; Renewable Energy; Sustainability; Electrical Power Engineering